2018
DOI: 10.5397/cise.2018.21.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Capsular Volume Measurements in Multidirectional Shoulder Instability

Abstract: BACKGROUND: In a previous study undertaken to quantify capsular volume in rotator cuff interval or axillary pouch, significant differences were found between controls and patients with instability. However, the results obtained were derived from two-dimensional cross sectional areas. In our study, we sought correlation between three-dimensional (3D) capsular volumes, as measured by magnetic resonance arthrography (MRA), and multidirectional instability (MDI) of the shoulder.METHODS: The MRAs of 21 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The volume of injectate used for direct shoulder MR arthrography varies in the literature, ranging from 8 to 15 ml, with some authors titrating to perceived resistance to the injection while monitoring distention with imaging [ 152 , 155 ]. A patient with chronic capsular laxity may have a higher injection capacity, whereas a patient with adhesive capsulitis may tolerate a smaller volume injectate [ 160 163 ]. In work with cadavers, a volume of 15 mL of intraarticular fluid has been described as optimal for dMRA, but little data exists comparing adequate joint distention with rates of contrast leakage [ 164 ].…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of injectate used for direct shoulder MR arthrography varies in the literature, ranging from 8 to 15 ml, with some authors titrating to perceived resistance to the injection while monitoring distention with imaging [ 152 , 155 ]. A patient with chronic capsular laxity may have a higher injection capacity, whereas a patient with adhesive capsulitis may tolerate a smaller volume injectate [ 160 163 ]. In work with cadavers, a volume of 15 mL of intraarticular fluid has been described as optimal for dMRA, but little data exists comparing adequate joint distention with rates of contrast leakage [ 164 ].…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
“…9 ). Prior studies have shown an increased capsular volume on dMRA in MDI patients [ 160 , 193 ]. In particular, greater inferior and posteroinferior axillary recess depths have been accurate and reproducible in differentiating MDI from control groups [ 161 , 193 195 ].…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods have been previously reported; some authors have shown how an increased capsular volume, expressed as the three-dimensional capsular volume with respect to glenoid surface, and an increased sagittal cross-sectional capsular area are related to MDI [8,14]. However, they also observed that the glenoid surface area is not significantly different in patients with or without atraumatic instability.…”
Section: Discussionmentioning
confidence: 99%
“…The width of the rotator interval has been previously studied on both traumatic [15] and atraumatic shoulder. Patients with chronic anterior traumatic instability have been proven to have an increased rotator interval height, area, and index [13]; also, patients with multidirectional atraumatic instability have increased width and depth of rotator interval and superior capsular elongation, compared to patients without instability [12,14,16]. We do not find statistically significant difference in terms of rotator interval width between patients with and without atraumatic shoulder instability, in line with a previous study by Provencher et al, who found no difference of rotator interval dimension expressed as the shortest distance between the anterior edge of the supraspinatus tendon and the superior edge of the subscapularis tendon [17].…”
Section: Discussionmentioning
confidence: 99%